9(6+x)=9x+54

Simple and best practice solution for 9(6+x)=9x+54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(6+x)=9x+54 equation:



9(6+x)=9x+54
We move all terms to the left:
9(6+x)-(9x+54)=0
We add all the numbers together, and all the variables
9(x+6)-(9x+54)=0
We multiply parentheses
9x-(9x+54)+54=0
We get rid of parentheses
9x-9x-54+54=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 3+p=6.23 | | 3x+2=x-110 | | 2(b+6)=16 | | x+26+131=180 | | 7(2p+3)-8=6p+28 | | x3-2=10 | | 2x-8=5x+8 | | 3x4x2=6x2 | | 10x^2−11x+1=0 | | x/2+11=13 | | -6y-5(5y-4)=-6-3(5y-y) | | 2x+6=2x-9 | | 1.2/3.5=x/7 | | -56=8x-68 | | -3y+15=y-17 | | 3x-6x-37=20 | | 1/4(8x+24)=13 | | 8x/5=2/4 | | 15x-2=11x-34 | | 6(w+8)+9w=2 | | 4(1+3x)+2x=5(2x+6) | | –3n=–45 | | -22=2x-20 | | 22=2x-20 | | 16=4x+32 | | 4x+6=34+8x | | 2x+3=-6x-3 | | 34–12+(-4)–(-2)+e=0 | | -4y-7=-7-4y | | x+1.7=13 | | -4y-7=-7-47 | | 15x-2=11x34 |

Equations solver categories